FAKTOR-FAKTOR YANG MEMPENGARUHI FOREIGN DIRECT INVESTMENT DI INDONESIA, 2008-2013 - , NEINI UTAMI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to analyze determinants of FDI in 33 provinces in Indonesia, 2008-2013. The independent variables which thought to have an influence on FDI is regional GDP per capita, road infrastructure, BPK opinion, the provincial minimum wage, public credit (investment, working capital, and consumption), public savings, capital expenditures budgeting, exports, inflation, and domestic private investment. The analytical tool used is multiple regression models with fixed effect method. The data is data panel of 33 Provinces in Indonesia in 2008-2013. The results showed that there are six variables were found to significantly affect the FDI, the public savings, the provincial minimum wage, domestic private investment, regional GDP per capita, exports and public credit Public savings, the provincial minimum wage, and domestic private investment proved to be negatively affected. The increase in these three variables has opposite direction with FDI. So, when the public savings, UMP and domestic investment rises, then FDI tend to go down. On the other hand, regional GDP per capita, exports and public credit has a positive influence on FDI, so those three variablesâ increases will cause FDI rise up. Keywords: FDI, income per capita, road infrastructure, BPK opinion, UMP, credit, savings, capital expenditures, GDP, exports, inflation rates, domestic private investment, panel data, fixed effect models